Official statement the amendment of Academic calendars semester II and short semester, 2020 2021 Academic session - Siti Nur Azwin, Zulkapri (2021)
1. The Ministry of Higher Education (MoHE) has recently issued a statement on the implementation of the teaching and learning (T&L) activities at Malaysian higher learning institutions. Based on the statement, Semester II, 2020/2021 Academic Session at UMP will commence on Monday, 1 March 2021, as previously announced.